Focal Targeting of the Bacterial Envelope by Antimicrobial Peptides - Rashid, Rafi; Veleba, Mark; Kline, Kimberly A. (Frontiers in Cell and Developmental Biology, 2016)
Antimicrobial peptides (AMPs) are utilized by both eukaryotic and prokaryotic organisms. AMPs such as the human beta defensins, human neutrophil peptides, human cathelicidin, and many bacterial bacteriocins are cationic and capable of binding to anionic regions of the bacterial surface. Cationic AMPs (CAMPs) target anionic lipids (e.g. phosphatidylglycerol (PG) and cardiolipins (CL)) in the cell membrane and anionic components (e.g. lipopolysaccharide (LPS) and lipoteichoic acid (LTA)) of the cell envelope. Bacteria have evolved mechanisms to modify these same targets in order to resist CAMP killing, e.g. lysinylation of PG to yield cationic lysyl-PG and alanylation of LTA. Since CAMPs offer a promising therapeutic alternative to conventional antibiotics, which are becoming less effective due to rapidly emerging antibiotic resistance, there is a strong need to improve our understanding about the AMP mechanism of action. Recent literature suggests that AMPs often interact with the bacterial cell envelope at discrete foci. Here we review recent AMP literature, with an emphasis on focal interactions with bacteria, including (1) CAMP disruption mechanisms, (2) delocalization of membrane proteins and lipids by CAMPs, and (3) CAMP sensing systems and resistance mechanisms. We conclude with new approaches for studying the bacterial membrane, e.g., lipidomics, high resolution imaging and non-detergent-based membrane domain extraction.